Coercive solvability of a generalized Cauchy-Riemann system in the Space $L_p (E)$ - Ospanov, K. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For an inhomogeneous generalized Cauchy-Riemann system with nonsmooth coefficients separated from zero, we establish conditions for the solvability and estimation of a weighted solution and its first-order derivatives.